First report: robotic pelvic exenteration for locally advanced rectal cancer. (January 2014) - Shin, J. W.; Kim, J.; Kwak, J. M.; Hara, M.; Cheon, J.; Kang, S. H.; Kang, S. G.; Stevenson, A. R. L.; Coughlin, G.; Kim, S. H.
Abstract Aim The aim of this study was to present the feasibility and surgical outcome of robotic en bloc resection of the rectum and with prostate and seminal vesicle invaded by rectal cancer. Method The details of three consecutive cases involving male patients in their forties, with locally invasive low rectal cancers are presented. The da Vinci robotic system was used by experienced colorectal and urological surgeons to perform en bloc resection of the rectum, prostate and seminal vesicles. Results In the first case, coloanal and vesico‐urethral anastomoses were performed, and the second included an end colostomy and vesico‐urethral anastomosis. The bladder and bulbar urethra were also removed en bloc in the third case, with robotic intracorporeal ileal conduit formation and end colostomy. There was no major complication postoperatively. In the second patient there was a minor leakage at the vesico‐urethral anastomosis. The third was readmitted the following week with a urinary infection which settled with intravenous antibiotics. In the first case, the circumferential resection margin was microscopically positive but the patient is currently free of recurrence after 14 months. In the second and third cases, all margins were clear. Conclusion This the first report of the use of the da Vinci robotic system for pelvic exenteration in patients with locally advanced rectal cancer invading the prostate and seminal vesicles. The robot may have a potential role in selected patients requiring exenterative pelvic surgery particularly in men.